2014
DOI: 10.1111/jicd.12087
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between levels of neuropeptide Substance P in periodontal disease and chronic pain: a literature review

Abstract: The aim of the current review was to investigate the relationship between levels of neuropeptide Substance P in periodontal disease and chronic pain. Substance P is a neuropeptide that is directly related with pain. In periodontal disease, it is expressed during the inflammatory process, and is one of the factors responsible for bone resorption. Studies have shown that Substance P levels are highest in the gingival crevicular fluid from sites with active periodontal disease and bone loss. The persistence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 69 publications
(154 reference statements)
0
15
0
Order By: Relevance
“…While substance P is mostly known for its role in pain and neurogenic inflammation and is found in the central nervous system ( Mantyh, 2002 ), it also mediates effects via receptors in non-neuronal tissues. Substance P modulates cell proliferation and cytokine production, mediates interaction between immune cells and neurons ( de Avila et al, 2014 ; Mashaghi, 2016 ) and is involved in immunoregulation ( Payan and Goetzl, 1985 ; Stead et al, 1987 , 1989 ; Haines et al, 1993 ; Ho et al, 1997 ; Schratzberger et al, 1997 ). The main receptor for substance P is neurokinin 1 receptor (NK1R), which belongs to the tachykinin receptor family of G protein-coupled receptors.…”
Section: Investigation Of C-fiber-derived Neuropeptides As Novel Pulmmentioning
confidence: 99%
“…While substance P is mostly known for its role in pain and neurogenic inflammation and is found in the central nervous system ( Mantyh, 2002 ), it also mediates effects via receptors in non-neuronal tissues. Substance P modulates cell proliferation and cytokine production, mediates interaction between immune cells and neurons ( de Avila et al, 2014 ; Mashaghi, 2016 ) and is involved in immunoregulation ( Payan and Goetzl, 1985 ; Stead et al, 1987 , 1989 ; Haines et al, 1993 ; Ho et al, 1997 ; Schratzberger et al, 1997 ). The main receptor for substance P is neurokinin 1 receptor (NK1R), which belongs to the tachykinin receptor family of G protein-coupled receptors.…”
Section: Investigation Of C-fiber-derived Neuropeptides As Novel Pulmmentioning
confidence: 99%
“…Substance P is closely related to neurogenic inflammation and plays a key role in the immune system by regulating the proliferation, migration and activation of immune cells [3]. A number of studies have shown that substance P, which is involved in inflammatory responses [4], exerts certain regulatory functions, such as increasing vascular permeability, affecting vasodilation [5,6], and inducing angiogenesis [7]. One study found that substance P may have a role in the pathogenesis of periodontal disease [8].…”
Section: Introductionmentioning
confidence: 99%
“…SP is a member of tachykinin family and is known to be extensively involved in the neurogenic inflammatory process [ 11 ]. Upregulated SP levels in synovium and synovial fluid (SF) have been observed in patients with RA [ 12 ]. In addition, SP has been demonstrated to facilitate vasodilatation and plasma extravasation into the synovial cavity, which probably contributes to arthritis progression [ 13 ].…”
Section: Introductionmentioning
confidence: 99%